The oral microbiota : a literature review for updating professionals in dentistry-Part II = La microbiota oral : una revisión de literatura para la actualización de profesionales en odontología-Parte II - Barboza Solís, Cristina 1986-
In the first part of this literature review, published in October 2019 in this journal, we summarized the conceptual background of the oral microbiota, and the main methods used in microbiology to characterize oral organisms. We also presented the most studied bacteria species in the oral microbiota. In this second part, we will discuss the evidence regarding the biological plausibility linking the oral microbiota dysbiosis and systemic diseases, as well as the main factors and mechanisms suspected in this association.